In Vitro Immunomodulatory Activity of Virgin Coconut Oil (VCO) with and without Bromelain Enzyme from Pineapple Waste (Ananas comosus (L) Merr) - Gustria Ernis; Devianri M; Nurul Afiatun Hasanah; Dyah Fitriani; Doni Notriawan; Deni Agus Triawan (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Immunomodulators are an essential part of the prevention process for treating various diseases related to the body’s immune system. This study aimed to determine the immunomodulatory activity of virgin coconut oil (VCO) with and without the enzyme bromelain in pineapple waste extract on the proliferation of mice lymphocyte cells through an in vitro test. VCO was made using two methods: enzymatic using bromelain enzyme (VCOb) from pineapple waste with 10, 25, and 50%, and mixing method without bromelain enzyme (VCOm). The two types of VCO produced were calculated for the yield, moisture content, free fatty acids (FFA), and physicochemical properties. For immunomodulatory activity, the test solution was taken from VCOb and VCOm with a variation concentration of 6.25, 12.5, 25, 50, and 100 µg/mL. Isolation of lymphocyte cells was obtained from the spleen organ of Swiss Webster strain mice which was performed aseptically with a ketamine-xylazine anesthetic. The lymphocyte cell proliferation test was performed using the MTT Assay, and the Optical Density was measured using a microplate reader at 550 nm. The results showed that 50% VCOb produced the highest yield and 22.22% higher than VCOm. However, the results showed that increasing bromelain enzyme concentration would increase the moisture content and free fatty acid content, but still below 0.2%. The VCOb and VCOm had immunomodulatory activity against mice lymphocyte cell proliferation. However, the immunomodulatory activity of VCO with bromelain enzyme from pineapple waste extract (VCOb) was higher than without bromelain enzyme (VCOm). The highest immunomodulatory activity was obtained at 100 µg/mL of VCOb with a percentage increase of 158.26% compared to negative controls, followed by VCOm of 100 µg/mL with a percentage increase of 137.66% compared to negative controls. The optimum dose of VCOm and VCOb for increasing the proliferation of mice lymphocyte cells has not been found.